PENGARUH KETIDAKAMANAN KERJA DAN STRES KERJA TERHADAP INTENSI KELUAR KARYAWAN PT. PADASA ENAM UTAMA MEDAN - Wawan Setiawan; Amirudin; Mella Yunita (BORJUIS: JURNAL OF ECONOMY, 2026)
This study aims to examine the influence of job insecurity and job stress on employee turnover intentions at PT. Padasa Enam Utama Medan. This is a quantitative study with a descriptive approach. The population in this study was all employees working at PT. Padasa Enam Utama Medan. The sampling technique used the purposive sampling method. The sample in this study consisted of 85 respondents. The data used in this study were primary data collected through a direct questionnaire survey. The results of the study, using multiple linear regression analysis, indicate that job insecurity and job stress have a positive and significant effect on turnover intentions. Based on the SPSS output, the RS-square value is 0.708 or R2 x 100% of 70.8%. This means that the independent variables in this study contribute significantly to explaining employee turnover intentions at PT. Padasa Enam Utama Medan, with the remaining 29.2% influenced by factors outside this study. In other words, there are still other independent variables that influence turnover intentions.